Epidemiological variables and clinical, haematological and urinary alterations in dogs seropositive for Leptospira spp - Langoni, Hélio; Silva, Aristeu Vieira da; Segismundo, Renata; Lucheis, Simone Baldini; Paes, Antonio Carlos (Semina: Ciências Agrárias, 2013)
In order to determine antibodies anti-Leptospira spp. in dogs from Botucatu-SP with a clinical suspicion and the risk factors for this zoonosis, as well possible hematological and urine alterations were collected blood samples from 248 dogs. The diagnostic test performed was the Microscopic Agglutination Test with 29 serovars of leptospires. Titers were considered reagent ?200 and detected in 17.7% (44/248) of the dogs. The most frequent serovars were Autumnalis (20.5%); Pyrogenes (18.2%); Gryppothyphosa (15.9%); Canicola (13.6%); Bratislava and Copenhageni (9.1%); Andamana (4.5%) and Djasiman (2.3%). Regarding the analysis of the epidemiological questionnaire administered to owners of the dogs, there was statistical significance for sex, age and presence of rats at home, showing that, by logistic regression analysis, only the sex variable was been significantly associated to the presence of antibodies anti-Leptospira. The levels of urea and creatinine were significantly increased in the group of animals reagents to the Microscopic Agglutination Test, showing the renal damage in these animals and decreased hemoglobin level.